KEANEKARAGAMAN JENIS BURUNG PADA DUA TIPE HABITAT DI KAWASAN GUNUNG MAYANA KABUPATEN KUNINGAN - Santoso, Rio; Supartono, Toto; Nurdin, Nurdin (Wana Raksa, 2023)
Abstract Mayana Mountain is an area which have several profit, such as ecological or economic aspects. And also as a habitat for several types of bird. The method of this research was used list of types of bird method (Mackinnon et al 2010). The types of bird which have found in Mayana Mountain Area were 31 types. The highest variety was community forest habitat, where have found 27 types and natural forest habitat was found 21 types. The value of  Index Shannon weiner was  average level, because the both of habitat have a grade as follow 1 <H' ≤ 3, where variety index of community forest habitat 2.94 and natural forest habitat 2.85. The level of species equality in the both of habitat was 17.0%, it belongs to low categories. To avoid the decrease of variety of protected species, especially for habitat of bird and for further research, increasing bird preversation intensively and sustainable.Pegunungan Mayana merupakan kawasan yang mempunyai banyak manfaat, baik dari segi ekologi maupun ekonomi. Dan juga sebagai habitat beberapa jenis burung. Metode penelitian yang digunakan adalah metode daftar jenis burung (Mackinnon et al 2010). Jenis burung yang ditemukan di Kawasan Pegunungan Mayana sebanyak 31 jenis. Keanekaragaman tertinggi terdapat pada habitat hutan rakyat yang ditemukan sebanyak 27 tipe dan habitat hutan alam sebanyak 21 tipe. Nilai Indeks Shannon weiner tergolong rata-rata, karena kedua habitat tersebut mempunyai nilai 1 <H' ≤ 3, dimana indeks keanekaragaman habitat hutan rakyat 2,94 dan habitat hutan alam 2,85. Tingkat kesetaraan spesies pada kedua habitat tersebut sebesar 17,0%, termasuk dalam kategori rendah. Untuk menghindari berkurangnya keanekaragaman jenis satwa yang dilindungi khususnya untuk habitat burung dan untuk penelitian lebih lanjut, meningkatkan pelestarian burung secara intensif dan berkelanjutan.